(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
This project presents a new medical image resolution enhancement technique based on the interpolation of the high-frequency subbands obtained by discrete wavelet transform (DWT) and the input image. The proposed resolution enhancement technique uses DWT to decompose the input image into different subbands. Then, the high-frequency subband images and the input low-resolution image have been interpolated, followed by combining all these images to generate a new resolution-enhanced image by using inverse DWT. In order to achieve a sharper image, an intermediate stage for estimating the high-frequency subbands has been proposed. The proposed technique has been tested on medical benchmark images. The visual results show the superiority of the proposed technique over the conventional and state-of-art image resolution enhancement techniques.